A transpirometer - theoretical principles and technical feasibility - Mangueira, Dulcidio de Souza; Silans, Alain M. B. Passerat de (Pesquisa Agropecuaria Brasileira, 1995)
In this paper an apparatus for measuring sap flow in an intact sugarcane plant, i.e. for measuring daily transpiration of the plant, is described. Principles of this apparatus are based on heat balance equation applied on an electrically heated slide of the plant. Heat flux is dissipated in axial conductive and convective fluxes, the latter beeing proportional to the sap flux. Heat fluxes are calculated from termo-couple measurements from which electrical signals are registered in an A.D. conversor into a microcomputer. Sensibility of the apparatus is studied regarding several factors. Experimental values are compared with theoretical ones from a temperature dissipation model. We concluded on the feasibility of the apparatus.